INFLUENCE INFLATION OF COMPOSITE STOCK SHARE PRICE INDEX LISTED IN BEI JAKARTA - Nurhana Dhea Parlina (JURISMA : Jurnal Riset Bisnis & Manajemen, 2013)
Inflation is factor that influence the (IHSG) Composite Stock Share Price Index. Above also explains, if Inflation rates rise then the Composite Stock Share Price Index will go up, but we see that the theory will not be the same forever with the practice or application. For that we intend to see if it was true what was mentioned by the theory. To find out we took Composite Stock Share Price Index data that listed on BEI Jakarta from the period 1 January 2013 - until 31 December 2015. Then we took the Inflation rate data from the period 1 January 2013 - until 31 December 2015.Inflation is the one of economic factor can influence Composite Stock Share Price Index. If the inflation more high than before it can impact of Composite Stock Share Price Index. Otherwise, In this study we will examine Composite Stock Share Price Index from the results obtained output of coefficient over than 0.05 as much as 0.159 so the final inflation isn’t influence of Composite Stock Share Price.